Toward a New Geographic Classification of Dialectal Groups in the Sultanate of Oman - Alkathiri, Amir (Al-Adab Journal, 2024)
This study aims to propose a new geographical classification of dialectal groups in the Sultanate of Oman, building upon the classification established by Clive Holes (1989), which categorized these dialectal groups in northern and central Oman into four dialectal groups based on phonological and morphological linguistic levels, namely, two Bedouin and two urban groups. The current study intends to investigate a number of linguistic units employed by Clive Holes within the geographic scope he defined, covering 15 specific geographic locations. This investigation aims to compare the points of agreement and divergence between the current study and Holes’ work. Additionally, the study seeks to document the spoken manifestations of these linguistic units within a broader geographic scope than that delineated by Holes. This expanded scope includes the dialectal groups in the Dhofar and Al Batinah governorates, which Holes excluded from his research. The linguistic data for this study were collected during field visits conducted by the present researcher between 2018 and 2019 to various governorates in the Sultanate of Oman. Based on the linguistic units examined, the study concludes that some of the categories identified by Holes as single dialectal groups can be reclassified into two or more distinct dialectal groups. For example, what Holes referred to as a single Bedouin group, the current study classifies into three separate dialectal groups: the Bedouin group in the Al Buraimi governorate, the Bedouin group in the northern Al Batinah governorate, and the Bedouin group in the South Al Sharqiyah governorate. Furthermore, the study introduces a new urban dialectal group within the urban geographic scope defined by Holes, which encompasses the urban group in the Dhahirah governorate and the connected mountainous areas in the Al Khaborah wilayat of the northern Al Batinah governorate. In addition to these modifications, the study also identifies dialectal groups in regions previously excluded by Holes, such as the urban group in the Musandam governorate and both urban and Bedouin groups in the Dhofar governorate. It is likely that some of these differences can be attributed to phonological and morphological developments that occurred between Holes’ study and the current research period.